1999
DOI: 10.1023/a:1007103009313
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Carcinoembryonic antigen (CEA) and tissue polypeptide antigen (TPA) levels in serum and urine from 25 patients with bladder cancer and 42 patients with cancer of the renal pelvis/ureter have been evaluated as an aid for clinical diagnosis of urothelial cancer. The tumour CEA content varied markedly, from values obtained in normal urothelium up to 822 and 7306 ng/g wet tissue in cancer of the renal pelvis/ureter and bladder cancer, respectively. Serum and urine CEA levels were found not to correlate with the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The weighted mean values for sensitivity and specificity are 84.1% and 96.6%, respectively (based on 277 cases and 311 controls). However, Stefanovic et al reported that TPA lacks diagnostic accuracy [ 62 ], and Carbin et al reported that TPA is only effective if 24 hour urine samples are analysed [ 63 ]. Additionally, although the averaged sensitivity/specificity appear higher than the averaged sensitivity/specificity for other cytokeratin based tests (UBC and Cyfra 21-1), in a direct comparison of TPA and Cyfra 21-1 Sanchez-Carbayo found TPA to be slightly inferior to Cyfra 21-1, indicating that the equivocal studies have overestimated the performance of TPA [ 61, 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…The weighted mean values for sensitivity and specificity are 84.1% and 96.6%, respectively (based on 277 cases and 311 controls). However, Stefanovic et al reported that TPA lacks diagnostic accuracy [ 62 ], and Carbin et al reported that TPA is only effective if 24 hour urine samples are analysed [ 63 ]. Additionally, although the averaged sensitivity/specificity appear higher than the averaged sensitivity/specificity for other cytokeratin based tests (UBC and Cyfra 21-1), in a direct comparison of TPA and Cyfra 21-1 Sanchez-Carbayo found TPA to be slightly inferior to Cyfra 21-1, indicating that the equivocal studies have overestimated the performance of TPA [ 61, 62 ].…”
Section: Resultsmentioning
confidence: 99%